2020
DOI: 10.5430/ijfr.v11n4p421
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Earnings Quality and Debt Maturity on Investment Efficiency: Study Case in Vietnam

Abstract: The paper analyzed the impact of earnings quality (EQ), debt maturity, investment efficiency (IE) of listed companies on Vietnam stock market thanks to the regression methods of FEM, REM and GLS and data of enterprises in the period of 2010 - 2018. The research findings have shown that EQ and debt maturity have a positive impact on EI, in which EQ has a stronger influence than debt maturity. A review of both EQ and the debt maturity for overinvestment or underinvestment indicated a positive impact and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 34 publications
2
17
0
1
Order By: Relevance
“…Al 'Alam & Firmansyah (2019), Gomariz & Ballesta (2014), Hung et al (2020), Jafari (2016), Suaidah & Sebrina (2020) concluded that debt maturity positively influences investment efficiency. The company's use of short-term debt can overcome the underinvestment problem owned by the company (Al 'Alam & Firmansyah, 2019).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Al 'Alam & Firmansyah (2019), Gomariz & Ballesta (2014), Hung et al (2020), Jafari (2016), Suaidah & Sebrina (2020) concluded that debt maturity positively influences investment efficiency. The company's use of short-term debt can overcome the underinvestment problem owned by the company (Al 'Alam & Firmansyah, 2019).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…The company's use of short-term debt can overcome the underinvestment problem owned by the company (Al 'Alam & Firmansyah, 2019). Short-term debt has requirements that tend to be easy so that it is fast to fulfill and has a quick disbursement process (Hung et al, 2020). Therefore, short-term debt will more quickly provide the company with a source of funds that can increase the efficiency of the company's investment.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Penelitian sebelumnya sudah menguji efisiensi investasi dengan beberapa faktor seperti kualitas laporan keuangan (Gusmawan & Novita, 2017;Aulia & Siregar, 2018;Shahzad et al, 2019;Sitorus & Murwaningsari, 2019;Assad & Alshurideh, 2020;Fajriani et al, 2021;Akasumbawa & Haryono, 2021), kepemilikan keluarga (Shahzad et al, 2019), kualitas audit (Assad & Alshurideh, 2020), insentif pajak (Sitorus & Murwaningsari, 2019), tata kelola perusahaan (Sitorus & Murwaningsari, 2019;Akasumbawa & Haryono, 2021), diversitas gender (Gusmawan & Novita, 2017), koneksi politik (Saputri, 2020), kepemilikan institusional (Simanungkalit, 2017;Fajriani et al, 2021), maturitas utang (Aulia & Siregar, 2018;Hung et al, 2020;Fajriani et al, 2021;Akasumbawa & Haryono, 2021), kualitas informasi akuntansi (Elaoud & Jarboui, 2017;Saputri, 2020;Hidayat & Mardijuwono, 2021), komite audit, komisaris independen, dan kepemilikan manjerial (Simanungkalit, 2017), kualitas laba (Hung et al, 2020), karir Chief Executive Officer (CEO) (Aulia & Siregar, 2018), spesialisasi auditor (Elaoud & Jarboui, 2017), kepemilikan asing (Tran, 2020), karakteristik manajemen (Lai & Liu, 2017), kepemilikan negara dan kepercayaan sosial (Fonseka et al, 2021). Penelitian ini bertujuan untuk menguji tentang adanya pengaruh kualitas laporan keuangan terhadap efisiensi investasi mengingat masih terdapat perbedaan (inkonsistensi) hasil dengan penelitian sebelumnya sehingga masih diperlukan pengujian kembali.…”
Section: Pendahuluanunclassified